Photocatalytic study of some synthesized MWCNTs/TiO2 nanocomposites used in the treatment of industrial hazard materials - Badr A. El-Sayed; Walied A.A. Mohamed; Hoda R. Galal; H.M. Abd El-Bary; Mahmoud A.M. Ahmed (Egyptian Journal of Petroleum)
Multi-walled carbon nanotubes/titanium dioxide nanocomposites were successfully synthesized by Sol-Gel method using new different ratios of tetrabutyl titanate and functionalized MWCNTs as the starting precursors. The synthesized Multi-walled carbon nanotubes/different titanium dioxide percentages (MWCNTs/3, 6 and 10%TiO2) nanocomposites were characterized using XRD, SEM and N2 Adsorption-Desorption techniques. The optical band gap was estimated for MWCNTs and MWCNTs with different TiO2 percentages by Kubelka-Munk equation giving 3.72, 2.92, 2.83, 2.71 eV values respectively. The synthesized nanocomposites were used as photocatalyst for decontamination of two local textile Dianix Blue and Vat Green 1 Dyes which commonly used in dyeing manufacture in local market. Keywords: MWCNTs/x%TiO2 nanocomposites, Sol–gel method, BET, Dianix Blue Dye, Vat Green 1 Dye